Distribusi, Promosi, dan Periklanan Pesan Wakaf pada Masyarakat Badan Wakaf Indonesia Kota Tangerang Selatan - Nurochman Nurochman; Andi M. Faisal Bakti (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2026)
Waqf is one of the instruments of Islamic economics that holds great potential for improving community welfare and promoting sustainable socioeconomic development. However, this potential has not been fully realized due to low public participation in waqf. This situation indicates that messages and education regarding waqf have not been effectively communicated to the general public. This study aims to analyze how the distribution, promotion, and advertising of waqf messages are conducted to the public through a case study of the Indonesian Waqf Board in South Tangerang City. The method used is a descriptive qualitative approach with a constructivist paradigm. Data collection was conducted through interviews, observations, documentation, and literature review to obtain a comprehensive picture of the waqf communication strategies implemented. The results of the study indicate that the distribution of waqf messages is still limited to seminars, workshops, and incidental activities, resulting in uneven information reach. Waqf promotion has also not been conducted consistently and remains conventional, while the use of digital advertising and social media has not been maximized. The main obstacles faced include low public literacy regarding waqf, a lack of professionalism among waqf administrators, and minimal public trust in waqf management. This study concludes that the development of waqf requires modern communication strategies through the digitization of messages, consistent promotion, increased institutional transparency, and intensive use of social media in order to significantly increase public participation in waqf.